Poetry as method in the History classroom: Decolonising possibilities (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Poetry can present historical material in a non-academic format. This format may be particularly important for students who are excluded from epistemic access (Morrow, 2007). This exclusion stems from many things, but ways of writing, ways of framing history, and whose voices and stories are heard are part of this exclusion. This article explores using poetry as a method of decolonising history teaching, primarily in teacher training classroom contexts. Poetry provides a unique combination of orality, personal perspective, artistic license, and historical storytelling. The form can also draw students into a lesson. As a device somewhat removed from students’ ideas about what history is, poetry is an alternative way of investigating ideas of “truth”, evidence, narrative, and perspective. It provides an entry point to historical topics, that can be supplemented through other texts and forms of evidence. Poetry also provides a voicing for sensitive topics, acknowledges and embraces complexity and pain. It could also remove the teacher as mediator, even if only for a moment. Additionally, it can open space for marginalised voices and stories. By drawing from local poems, especially by black womxn poets, race and gender are centred in the conversation in a visceral way. International poets open conversations about globally linked histories. Poets from different generations raise questions of continuity and change. All poems are open to examination through historical thinking skills. This article explores the tensions in decolonising the Curriculum Assessment Policy Statement (CAPS) history Further Education and Training (FET)(Senior High School) curriculum and in using a creative medium such as poetry to do so.
Keywords: Decolonisation; History; Teacher education; South Africa; Curriculum; Poetry; Pedagogy; Historical thinking